The Effect of Using Palm Shell Fly Ash with Crushed Fine Aggregate on the Compressive Strength of Concrete - Zulfira Mirani; mukhlis, Mukhlis; Oni Guspari; Wayu Aktorina; Lusyana; Enita Suardi; Lidiya Annisa; Monika Natalia (Universitas Negeri Padang, 2025)
Palm shell combustion waste produces fly ash containing chemical elements such as silica (SiO2) and aluminum oxide (Al2O3), which can act as pozzolanic material. Pozzolans are materials containing silica (SiO2) and aluminum oxide (Al2O3) that cannot harden or bind independently like cement when mixed with water, but can react with calcium hydroxide Ca(OH)2 produced from the hydration process of cement, forming cementitious compounds. This study aims to determine the effect of palm shell fly ash as a substitution material and additive on the compressive strength of concrete with crushed fine aggregate variation. The tests were conducted with fly ash content of 0%, 15%, 17.5%, 20%, 22.5%, and 25% of cement weight. All specimens were cured under standard conditions and tested at 28 days. The results showed that, with crushed fine aggregate, the compressive strength of concrete with 20% fly ash substitution reached 30.848 MPa, which is 39.15% higher than concrete with fly ash as additive (22.169 MPa). From an engineering standpoint, the optimal substitution level of 20% fly ash yields the highest compressive strength with crushed fine aggregate, providing valuable insight for practical mix design optimization. Although the compressive strength did not exceed that of plain concrete in all conditions, the performance improvement at certain substitution levels highlights the potential for fly ash to enhance durability, workability, and long-term strength development due to its pozzolanic reaction. However, compared with plain concrete without fly ash (24.166 MPa), the addition or substitution of fly ash did not result in higher strength overall. The findings of this study have several important implications for sustainable construction materials and the broader field of concrete technology. The utilization of palm shell fly ash as a partial cement replacement demonstrates the potential for converting agricultural waste into value-added construction materials. This supports environmental sustainability by reducing cement consumption, which is a major source of CO2 emissions, and by minimizing waste disposal problems from palm oil industries.